Fireless cookery - Rannells, Lulu Mahala; Kimball, Mary (My University, 1907)
Introduction: Fireless Cookery is not a new convenience in the art of cooking. In Germany the cooker was known by the name of a hay box. The very primitive box was lined with any cloth which happened to be convenient, filled with hay, a nest made in which the utensil with the particularly cooked food was placed, and hay packed on top of the utensil. The food was allowed to remain in the box a number of hours to complete the cooking. Our attention was drawn to the device by a United States Representative to Germany. Further experiment was made by the Commissary Department. The work was done at Fort Riley, Kansas by two of the instructing army cooks. The experiment was found…
Citation: Rannells, Lulu Mahala and Kimball, Mary. Fireless cookery. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Fireless Cookery; Easy Cooking; Cooking Technology; Theses; Manuscripts (documents)